STRESS ANALYSIS OF THE ROLLERS DURING COLD ROLLING BY USING FINITE BLEMENT METHOD (Journal of Engineering, 2003)
This work deals with the determination of contact stress distribution during symmetrical rolling processes using the finite element method ( FEM).The results give a clear idea for the type of distribution of the normal and shear stresses along thearc of contact ,for the rollers with a radial depth ratio (f) equal to ( 1,0.7, 0.4) .A study ot the deformation induced in the region of maximum shear stress together with the location of stress concentration and the maximum stress was achieved